Some numerical solutions of local fractional tricomi equation in fractal transonic flow - İnç, Mustafa; Korpinar, Zeliha; Almohsen, Bandar; Chu, Yu-Ming (Elsevier, 2021)
We investigate numerical solutions of fractional-order Tricomi equation (LFTE) in fractal transonic flow media by employing the method of local fractional q-homotopy transform (LFq-HATM). This method is a combination of methods of homotopy analysis and q-Laplace transform. We express the solutions in terms of rapidly convergent power series where the basics functions are easily computable by Mathematica software. We present uniqueness and convergence analysis of the model via Banach's fixed point theory (BFPT). Reliability analysis of the numerical method is provided by figures and physical works. Obtained results indicate the strength and efficiency of the LEq-HATM. (C) 2020 The Authors. Published by Elsevier B.V. on behalf of Faculty of Engineering, Alexandria University.
Keywords: Local fractional; Tricomi equation; Laplace transform (LT); Local fractional q -HATM; BFPT